PENGARUH LAMA PENYIMPANAN TERHADAP PERUBAHAN MORFOLOGI DAN KANDUNGAN GIZI PADA UMBI TALAS BOGOR (Colocasia esculenta (L.) Schott) - Jean Cafriany Suryana Putri; Sri Haryanti; Munifatul Izzati (Jurnal Akademika Biologi, 2017)
Storage of agricultural products is an important thing to do in post-harvest handling. Bogor Taro (Colocasia esculenta (L.) Schott) is a perishable agricultural products at harvest time, so it takes a good handling to be able to maintain its quality as a functional food ingredient (instead of rice). This study aims to determine the long effect of storage on morphology changes, proximate and vitamin B1 content of the tuber Bogor taro. The study design used Completely Randomized Design (CRD) for storage time of 5 days (K.I), 10 days (K.II) and 15 days (K.III) with three replications. The main parameters of the study are the morphological changes (weight loss, shrinkage diameter, tuber damage, the presence of buds) and the chemical changes (proximate and vitamin B1 content). The parameters also play a role in the form of environmental storage conditions (temperature, humidity and light intensity). The analysis of the data was done using Analysis of Variance (ANOVA) followed by further test of Duncan’s Multiple Range Test (DMRT) at the level of 95%. The result showed the long effect of different storage significantly affect weight loss, but didn’t significantly affect shrinkage diameter and cause tuber damage and growth of shoots. The long effect of different storage significantly affect water content and vitamin B1, but didn’t significantly affect the ash content, crude lipid content, crude protein content and crude fiber content. The duration of storage for 5 days (K.I) showed the best results in maintaining their nutritional value. Keywords: Bogor taro (Colocasia esculenta (L.) Schott), storage, proximate vitamin B1